LITERACY STRATEGY FOR POST-PANDEMIC “LEARNING LOSS" RECOVERY AT SD NEGERI WONOKERTO 2 PROBOLINGGO - Anggraeni, Prastika Ririt; Wicaksono, Arif (EDUCATUM: Scientific Journal of Education, 2023)
Learning loss is a situation where learners lose knowledge and skills either general or special or decline academically, which occurs due to prolonged gaps or discontinuity of the educational process. This study aims to examine and analyze literacy strategies for learning loss recovery in post-pandemic students at SD Negeri 2 Wonokerto. The method used is the observation method, this observation is done by directly observing the learning process in elementary school after re-entry to school and the implementation of limited face-to-face learning. Observation was conducted on Grade 6 students in SD Negeri 2 Wonokerto. From the observations made by the school literacy team (TLS) to create a literacy innovation program for the recovery of learning loss in post-pandemic students with the JIBAKU (required to read books) and SIGASA (language Guardian Students) programs, both literacy programs are considered effective in the recovery of learning loss in Grade 6 students at SDN 2 Wonokerto.